2015
DOI: 10.1002/chem.201501725
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Gold‐Catalyzed Propargyl Ester Rearrangement/Tandem Cyclization Sequence: Radical versus Gold Catalysis—Myers–Saito‐ versus Schmittel‐Type Cyclization

Abstract: A detailed study of the gold-catalyzed tandem 1,3-carboxy migration/allene-enyne cycloisomerization was undertaken. It was found that after the initial allene formation the selectivity of the reaction is strongly influenced by the polarization of the remaining alkyne. Depending on the substitution pattern of the starting diynes, either a Schmittel- or a Myers-Saito-type cyclization was triggered. The 6-endo-dig Myers-Saito-type cyclization gave access to benzo[b]fluorenes, while the Schmittel pathway (5-exo-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…Deprotonation and protodeauration of the ensuing carbocationic species VIa would then provide 5 a . We reason that a competitive 7‐ exo ‐ dig cyclization pathway leading to the tetradehydroazulene 14 a was not observed as it would require Au−C bond formation to occur at the slightly more electron‐rich distal alkynyl carbon center in IIa (Scheme , path d) . Added to this is the formation of the vinyl gold species VIIa , which might be anticipated to be less likely because of unfavorable steric interactions between the geminal phenyl group and metal complex in the proposed adduct.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Deprotonation and protodeauration of the ensuing carbocationic species VIa would then provide 5 a . We reason that a competitive 7‐ exo ‐ dig cyclization pathway leading to the tetradehydroazulene 14 a was not observed as it would require Au−C bond formation to occur at the slightly more electron‐rich distal alkynyl carbon center in IIa (Scheme , path d) . Added to this is the formation of the vinyl gold species VIIa , which might be anticipated to be less likely because of unfavorable steric interactions between the geminal phenyl group and metal complex in the proposed adduct.…”
Section: Figurementioning
confidence: 99%
“…All the above Au I ‐mediated reactions additionally demonstrated that the ring‐forming process occurred in a selective manner with only the partially hydrogenated 1 H ‐cyclopenta[8]annulene derivative being obtained. On the basis of NMR measurements of the crude reaction mixtures, other cyclization compounds such as those arising from a potentially competitive 7‐ exo ‐ dig cyclization or formal [3+2] cycloaddition pathway were not detected …”
Section: Figurementioning
confidence: 99%
“…At about the same time, Hashmi and co-workers illustrated 1,5-diyne esters 58 containing an ester moiety at the non-aromatic terminus, to undergo two distinct gold(I)-catalyzed cycloisomerizations to furnish benzo [b]fluorenes 59 and benzofulvenes 60 in combined yields of up to 96% (Scheme 15). [21] Realized in the presence of the i-PrAuCl and AgNTf 2 catalyst combination, the initial step of the proposed mechanism was reported to begin with a gold(I)-catalyzed 1,3-acyloxy shift in the substrate to afford allenyl intermediate 61. Further activation of the remaining alkyne moiety in the newly formed allene adduct by the metal complex was believed to initiate two potential cyclization pathways with the chemoselective outcome dependent on the electronic nature of the aryl tether.…”
Section: 40mentioning
confidence: 99%
“…A1-A3 shows the result of the cyclizative products with 1,3-carboxylate shift under metal-catalyzed conditions. 9 Recently, Liu groups reported base catalyzed Schmittel enyne-allene cyclization (Type A4). It has been assumed that acyl migration was occurred only under [Au and Pt] catalyzed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…reported benzofulvenes via 1,3‐acyl migration strategy (Type A3 ) through a Schmittel‐type (C 2 –C 6 ) enyne–allene cyclization by platinum‐catalyzed reaction . It has been postulated that Au(I)‐catalyzed [3,3]‐rearrangement of propargylic esters are reversible processes that take place via Au(I)‐coordinated cationic intermediates and subsequent formation of the allenes, which can then undergo further transformations . Recently, Liu groups reported base catalyzed Schmittel enyne–allene cyclization (Type A4 ) .…”
Section: Introductionmentioning
confidence: 99%